Rotten-fruit-sorting robotic arm: (Design of low complexity cnn for embedded system) - Amin, Muhammad Ihtisham; Hafeez, Muhammad Adeel; Awais, Qasim (MDPI, 2022)
Industrial Automation has revolutionized the processing industry due to its high accuracy, the time it saves, and its ability to work without tiring. Being the most fundamental part of automation machines, robotic arms are being used as a fundamental component in many types of domestic as well as commercial automation units. In this paper, we proposed a low-complexity convolutional neural network (CNN) model and successfully deployed it on a locally generated robotic arm with the help of a Raspberry Pi 4 module. The designed robotic arm can detect, locate, and classify (based on fresh or rotten) between three species of Mangos (Ataulfo, Alphonso, and Keitt), on a conveyor belt. We generated a dataset of about 6000 images and trained a three-convolutional-layer-based CNN. Training and testing of the network were carried out with MatLab, and the weighted network was deployed to an embedded environment (Raspberry Pi 4 module) for real-time classification. We reported a classification accuracy of 98.08% in the detection of fresh mangos and 95.75% in the detection of rotten mangos. For the designed robotic art, the achieved angle accuracy was 93.94% with a minor error of only 2°. The proposed model can be deployed in many food- or object-sorting industries as an edge computing application of deep learning.
Keywords: Convolutional Neural Networks; Edge Computing; Deep Learning; Fruit Sorting; Robotic Arm